Sulforaphane as a potential therapy for multiple sclerosis: a review article - Gede Febby Pratama Kusuma, Pratama Kusuma; Kadek Dede Frisky Wiyanjana; Sri Maliawan (Indonesian Archives and Biomedical Sciences, 2021)
Multiple Sclerosis (MS) is a chronic immune-mediated Neuroinflammatory disease that attacks the Central Nervous System (CNS). It creates serious physical disabilities characterized by neuronal injury, demyelination, and axonal loss. Several mechanisms are responsible for the progression of MS, including the infiltration of T-cells from the peripheral to the CNS, the autoreactivity of B-cells that contribute to abnormal regulation of antibodies and antigen presentation, and the assault of Macrophage that lead to inflammation and neuron damage. Additionally, oxidative stress plays a more important role in chronic inflammation of MS. Sulforaphane (SFN) is an isothiocyanate derived from glucoraphanin (GRA) that is found mostly in broccoli. SFN can act as an anti-inflammatory and anti-oxidant agent by activating the Nuclear factor-erythroid 2-(NF-E2-) Related Factor 2 (Nrf2). Nrf2 is expressed in the central nervous system and upregulated in response to inflammation and cerebral insults. Nrf2 binds to the antioxidant response element (ARE) which is a DNA promoter region of genes codifying antioxidant enzymes, which in turn can reduce oxidative stress. Several in vitro and in vivo studies show that SFN can increase the anti-inflammatory and anti-oxidant genes. Thus, SFN is very promising as a potential therapy for MS.